AN EXPERIMENTAL STUDY OF THE EFFICACY AND SAFETY OF VARIOUS ENDOSCOPIC HEMOSTASIS TECHNIQUES - A. I. Cherepanin; O. N. Antonov; M. S. Sineokaya (Неотложная медицинская помощь, 2016)
ABSTRACT. The treatment of bleeding peptic ulcers remains one of the pressing challenges in urgent surgery. Currently available endoscopic hemostasis modalities only partially meet the requirements of safety, efficiency and reliability, and therefore total and postoperative mortality rates are still high, both in our country, and around the world. The aim of the study was to identify the benefits and shortcomings of endoscopic radiofrequency energy exposure compared to standard hemostatic techniques used in the world practice to treat bleeding peptic ulcers.